Mapping of a new quantitative trait locus for resistance to malaria in mice by a comparative mapping approach with human chromosome 5q31-q33 - Hernández Valladares, M.; Rihet, P.; Ole-MoiYoi, O.K.; Iraqi, F.A. (Springer, 2004)
A number of linkage studies in human populations have identified a locus ( pfbi) on Chromosome 5q31-q33 controlling Plasmodiun falciparum blood infection levels. This region contains numerous candidate genes encoding immunological molecules such as cytokines, growth factors and growth-factor receptors. We have used an F(11) advance intercross line (AIL) population of mice infected with Plasmodium chabaudi to identify additional mouse quantitative trait loci (QTL) for control of parasitaemia on Chrs 11 and 18, which carry regions homologous to human Chr 5q31-q33. Herein, we report a novel QTL for parasitaemia control ( char8) on the mouse Chr 11, linked to marker D11Mit242, and involved in the clearance stages of the parasites from the bloodstream. Strikingly, several Th2 cytokines that are located within char8 have been identified to play a predominant role in the late stages of the infection.